2018
DOI: 10.1186/s12859-018-2509-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tumor cell line response to drug pairs with deep learning

Abstract: BackgroundThe National Cancer Institute drug pair screening effort against 60 well-characterized human tumor cell lines (NCI-60) presents an unprecedented resource for modeling combinational drug activity.ResultsWe present a computational model for predicting cell line response to a subset of drug pairs in the NCI-ALMANAC database. Based on residual neural networks for encoding features as well as predicting tumor growth, our model explains 94% of the response variance. While our best result is achieved with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 26 publications
3
109
0
Order By: Relevance
“…By analyzing feature weight parameters for the trained model, we found that predictions largely relied on specific compound substructural presence. This is in accordance with the previous research where Xia et al [14] reported that the compound descriptors provided the largest contribution to predictive ability of deeply-layered neural networks (deep learning). Figure 2 shows compounds containing such "high-importance" substructures, where substructures are highlighted in red.…”
Section: Comparison Of Descriptorssupporting
confidence: 93%
“…By analyzing feature weight parameters for the trained model, we found that predictions largely relied on specific compound substructural presence. This is in accordance with the previous research where Xia et al [14] reported that the compound descriptors provided the largest contribution to predictive ability of deeply-layered neural networks (deep learning). Figure 2 shows compounds containing such "high-importance" substructures, where substructures are highlighted in red.…”
Section: Comparison Of Descriptorssupporting
confidence: 93%
“…For example, Keine and colleagues [19] investigated the effect of polypharmacy on older adults with dementia or Alzheimer's disease and predicted the medication burden using ML. Other investigators [20][21][22] raised computational challenges with predicting the effects of drug combination (both synergism and antagonism) and suggested ML as an effective method for tackling the challenge when data are available. A recent review article [23] that assessed the applications of ML/AI in drug combinations revealed that most studies focus on predictive analytics (e.g., predicting the outcomes of drug combinations) as opposed to prescriptive analytics (e.g., optimizing the combinations of drugs).…”
Section: Related Workmentioning
confidence: 99%
“…In particular, Chiu et al [5] and Li et al [15] combined auto-encoder with deep neural networks to predict drug responses of genomically profiled cell lines and tumors. Xia et al [6] utilized deep neural encoders to combine genomic features together with drug profiles to predict cell lines' responses to drug pairs. Wang et al [16] applied DNN model to predict chemically induced liver toxicity endpoints from transcriptomic responses.…”
Section: Related Work Drug Response Prediction Based On Genomic Featuresmentioning
confidence: 99%
“…We describe them in details in the following sections. As mentioned in many previous studies [14,15,6], including drug descriptor features will overshadow the impact of genomic features, in this study, we focus on the impact of genomic features and only use one-hot encoding features for drugs and do not utilize any drug feature extractors. For virtual drug screening, our approach could be easily extended to include more features.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation